PENGARUH REKRUTMEN, SELEKSI DAN PENEMPATAN KARYAWAN TERHADAP KINERJA KARYAWAN KOPERASI SIMPAN PINJAM DARMA SUCI DI DESA DARMASABA BADUNG - I Kadek Andi Gunawan; Putu Agus Eka Rismawan; Ary Wira Andika (VALUES, 2023)
This study aims to determine the effect of recruitment, selection and placement of employees on the performance of Darma Suci Savings and Loans Cooperative employees in Darmasaba Badung Village. Independent variables include recruitment, selection and job placement. The dependent variable includes employee performance. The population in this study were all employees of the Darma Suci Savings and Loans Cooperative. The samples obtained in this study were 32 employees and had 1 chairman who was determined based on the saturated sampling method. The analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that recruitment, selection and job placement have a positive effect on employee performance at the Darma Suci Savings and Loans Cooperative, Darmasaba Badung Village.